Chromatographic Separation of the Novel Hypoglycemic Drug Mitiglinide in its Bulk Powder and Pharmaceutical Formulation: Forced Degradation and Validated Stability-Indicating HPTLC/Densitometry and HPLC/UV Methods. (1st April 2020) - Eissa, Maya S; Darweish, Eman; Elghobashy, Mohammed R; Shehata, Mostafa A
Abstract: Background: Mitiglinide (MTG) is one of meglitinides group which are used for treatment of type two diabetes mellitus. Objective: Mitiglinide (MTG) is a novel oral hypoglycemic drug. The present work adopts two stability-indicating chromatographic methods for determination of MTG after being exposed to forced degradation using 4 M methanolic HCl for 12 h. Methods: The first method is HPTLC/densitometry using methanol:chloroform:acetic acid (5:2.5:0.3 by volume) as the eluting system and silica gel 60 GF254 as the stationary phase; the separated bands were then scanned at 220 nm. The second method is HPLC/UV in which acetonitrile:methanol:0.05 M potassium dihydrogen orthophosphate (pH 3.5) (40:25:35 by volume) was used as the mobile phase and a Zorbax SB-C8 (250 × 4.6 mm, 5 µm) column as a stationary phase, at a flow rate of 1 mL/min and UV detection at 220 nm. Results: As a result of acid hydrolysis, two degradants were obtained. The first one was benzyl succinic acid to which this study was performed. The second one lacked configuration and was unreadable using UV spectrometry. Linearity was in the range of 8–48 µg/band MTG for HPTLC and 10–80 µg MTG for HPLC. LOD and LOQ values were 1.85 and 5.62 µg/band for the HPTLC method and 2.14 and 6.49 µg/mL for the HPLC method, respectively. The Recovery % was 100.03 ± 1.464 and 99.61 ± 1.44 using the HPTLC and HPLC methods, respectively. The relative standard deviations (RSD, %) for intra- and inter-day assays were 1.111 and 1.430 for the HPTLC method, respectively, and those for the HPLC method were 1.377 and 0.866, respectively. The RSD, %, for robustness testing was 1.162 (saturation time of mobile phase) and 1.592 (change in ratio of methanol content) for the HPTLC method and 1.377 (mobile phase composition), 1.713 (detector wavelength) and 1.770 (mobile phase flow rate) for the HPLC method. Conclusions: The adopted methods were successfully applied for the determination of MTG in its pure form, in presence of its acid degradant and in its tablet dosage form. Highlights: Statistical comparison between the results obtained from the developed methods and those obtained by the reported HPLC method showed no significance difference.